Increased distance of shooting on basketball jump shot - Alves Okazaki, V. H.; Felix Rodacki, A. L. (Journal of Sports Science & Medicine, 2012)
The present study analyzed the effect of increased distance on basketball jump shot outcome and performance. Ten male expert basketball players were filmed and a number of kinematic variables analyzed during jump shot that were performed from three conditions to represent close, intermediate and far distances (2.8, 4.6, and 6.4m, respectively). Shot accuracy decreased from 59% (close) to 37% (far), in function of the task constraints (p < 0.05). Ball release height decreased (p < 0.05) from 2.46 m (close) to 2.38m (intermediate) and to 2.33m (long). Release angle also decreased (p < 0.05) when shot was performed from close (78.92°) in comparison to intermediate distances (65.60°). While, ball release velocity increased (p < 0.05) from 4.39 m/s (close) to 5.75 m·s-1 (intermediate) to 6.89 m·s-1 (far). These changes in ball release height, angle and velocity, related to movement performance adaptations were suggested as the main factors that influence jump shot accuracy when distance is augmented.